Relevansi Penggunaan Undang-Undang No. 35 Tahun 2014 Tentang Perlindungan Anak Ditinjau Dari Kehidupan Bermasyarakat Di Indonesia - Aulia, Anisya; Pahroji, Dedi (Jurnal Ilmiah Wahana Pendidikan, 2026)
Child protection is a right that every child born into the world can receive. This protection must be implemented as early as possible in order to provide guarantees so that children can live, develop and participate with a sense of security. The existence of Law No. 35 of 2014 as an amendment to Law No. 23 of 2002 concerning child protection emphasizes the need for criminal sanctions and fines for crimes committed against children in social life, especially in Indonesia. The method used in this research is a normative method using a literature study process which refers to searching for sources through secondary data.